Analysis Donald Trump’s Speech on The New Us-China Trade Deal: Study of Modality - Njue Steeven Tarigan; Elisabeth Monica Hutahaean; Halimah br.Surbakti; Rahel Raphita Sinabutar; Meisuri Meisuri (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
Language plays a vital role in expressing emotions, facilitating communication, and conveying a speaker’s stance through modality. This study analyzes the use of modality in a political speech by Donald Trump regarding a new U.S.-China trade deal, delivered on May 12, 2025. Employing a descriptive qualitative method, the research investigates how modality reflects Trump's intentions, beliefs, and authority. Data were collected through indirect observation of a YouTube video titled “President Trump touts new US-China trade deal: We Opened Up China”, followed by transcription, identification, and categorization of modality types based on Palmer's (2013) framework: epistemic, deontic, and dynamic modality. The findings reveal that Trump uses epistemic modality to express speculation, deontic modality to convey obligation and prohibition, and dynamic modality to demonstrate capability and initiative. These elements function strategically to shape his image as a decisive and persuasive leader. The study supports previous findings that modality serves as a rhetorical device in political discourse, contributing to influence and narrative construction.